Divergence history of the Rufous-tailed Tailorbird (Orthotomus sericeus) of Sundaland: Implications for the biogeography of Palawan and the taxonomy of island species in general. (27th August 2014) - Lim, Haw Chuan; Chua, Vivien L.; Benham, Phred M.; Oliveros, Carl H.; Rahman, Mustafa Abdul; Moyle, Robert G.; Sheldon, Frederick H.
Abstract: The Rufous-tailed Tailorbird ( Orthotomus sericeus )—a Sunda endemic—is divided into 3 morphologically based subspecies: one in western Sundaland (Malay Peninsula, Sumatra, and associated islands), one from the Natuna Islands in the South China Sea, and one on Borneo, Palawan, and smaller islands of the Sunda continental shelf east of Borneo. Previous study, however, suggested that these subspecies do not conform to molecular genetic subdivisions of the species. We reexamined the morphology and performed molecular phylogeographic and multi-locus coalescent analysis of two subspecies of Rufous-tailed Tailorbird comprising populations on the Malay Peninsula, Sumatra, Borneo, and Palawan. We found (1) little morphological difference among the two subspecies, (2) no substantial genetic differences between the Borneo and western Sunda populations, but (3) marked genetic divergence between the Palawan and other populations. We conclude that the Bornean and western Sunda populations interbred extensively during Quaternary glacio-eustatic land connections, whereas the Bornean and Palawan populations did not. Unlike the other Greater Sunda Islands, Palawan has not been attached by a land bridge to the rest of Sundaland for at least one million years, and its relative isolation has prevented extensive intermixing between Palawan's and other Sunda populations. Thus, the Palawan population appears to be on its own evolutionary trajectory. The ability to demonstrate extensive interbreeding among some Sunda island populations, but not others, illustrates the practicality of testing Gill's (2014) "null hypothesis" that morphologically distinct populations on different islands are different species unless a compelling argument can be made to the contrary. In this case, Rufous-tailed Tailorbird morphology provided little or misleading evidence of the extent of interbreeding, whereas modern genetic analysis provided a clear view.